Essential role of the zinc transporter ZIP9/SLC39A9 in regulating the activations of Akt and Erk in B-cell receptor signaling pathway in DT40 cells. - Masanari Taniguchi; Ayako Fukunaka; Mitsue Hagihara; Keiko Watanabe; Shinichiro Kamino; Taiho Kambe; Shuichi Enomoto; Makoto Hiromura (PLoS ONE)
The essential trace element zinc is important for all living organisms. Zinc functions not only as a nutritional factor, but also as a second messenger. However, the effects of intracellular zinc on the B cell-receptor (BCR) signaling pathway remain poorly understood. Here, we present data indicating that the increase in intracellular zinc level induced by ZIP9/SLC39A9 (a ZIP Zrt-/Irt-like protein) plays an important role in the activation of Akt and Erk in response to BCR activation. In DT40 cells, the enhancement of Akt and Erk phosphorylation following BCR activation requires intracellular zinc. To clarify this event, we used chicken ZnT5/6/7-gene-triple-knockout DT40 (TKO) cells and chicken Zip9-knockout DT40 (cZip9KO) cells. The levels of Akt and ERK phosphorylation significantly decreased in cZip9KO cells. In addition, the enzymatic activity of protein tyrosine phosphatase (PTPase) increased in cZip9KO cells. These biochemical events were restored by overexpressing the human Zip9 (hZip9) gene. Moreover, we found that the increase in intracellular zinc level depends on the expression of ZIP9. This observation is in agreement with the increased levels of Akt and Erk phosphorylation and the inhibition of total PTPase activity. We concluded that ZIP9 regulates cytosolic zinc level, resulting in the enhancement of Akt and Erk phosphorylation. Our observations provide new mechanistic insights into the BCR signaling pathway underlying the regulation of intracellular zinc level by ZIP9 in response to the BCR activation.